A Leaf-Mimicking Method for Oral Delivery of Bioactive Substances Into Sucking Arthropod Herbivores - Ghazy, Noureldin Abuelfadl; Okamura, Mayo; Sai, Kanae; Yamakawa, Sota; Hamdi, Faten Abdelsalam; Grbic, Vojislava; Suzuki, Takeshi (Frontiers in Plant Science, 2020)
Spider mites (Acari: Tetranychidae) are pests of a wide range of agricultural crops, vegetables, and ornamental plants. Their ability to rapidly develop resistance to synthetic pesticides has prompted the development of new strategies for their control. Evaluation of synthetic pesticides and bio-pesticides—and more recently the identification of RNA interference (RNAi) target genes—requires an ability to deliver test compounds efficiently. Here we describe a novel method that uses a sheet-like structure mimicking plant leaves and allows for oral delivery of liquid test compounds to a large number of individuals in a limited area simultaneously (~100 mites cm−2). The main component is a fine nylon mesh sheet that holds the liquid within each pore, much like a plant cell, and consequently allows for greater distribution of specific surface area even in small amounts (10 µL cm−2 for 100-µm mesh opening size). The nylon mesh sheet is placed on a solid plane (e.g., the undersurface of a Petri dish), a solution or suspension of test compounds is pipetted into the mesh sheet, and finally a piece of paraffin wax film is gently stretched above the mesh so that the test mites can feed through it. We demonstrate the use of the method for oral delivery of a tracer dye (Brilliant Blue FCF), pesticides (abamectin and bifenazate), dsRNA targeting the Vacuolar-type H+-VATPase gene, or fluorescent nanoparticles to three species of Tetranychus spider mites (Acari: Tetranychidae) and to the cotton aphid, Aphis gossypii Glover (Hemiptera: Aphididae). The method is fast, easy, and highly reproducible and can be adapted to facilitate several aspects of bioassays.